Steadily cubic : a squared odyssey. Wittgenstein’s cube–examples - Krkač, Kristijan (Array, 2020)
In the paper, the author analyzes and compares cube examples in Wittgenstein’s works, especially the cube from TLP (TLP 1974 5.5432) and the cube from PPF (ex PI II) (PPF 2009 116). There is no direct evidence that the PPF–cube is a reaction to the “grave mistake” of the TLP–cube. Also, there is no evidence that the TLP–cube is a representation of the Necker’s cube (1832), although it resembles the Jastrow’s cube (1900). These are negative results. Both cubes present important ideas of TLP and PPF (PI). Also, Wittgenstein writes that he “purposely chose” the example of the cube in PI and PPF, perhaps to show one of the “grave mistakes” of the TLP–cube. By analysis of the Necker’s cube and comparison of drawings and accompanied text of the TLP–cube and the PPF–cube the author tries to explicate some possible implicit pictorial aspects of Wittgenstein’s thought and of the general nature philosophical thinking as pictorial.